Postexposure Efficacy of Recombinant Vesicular Stomatitis Virus Vectors Against High and Low Doses of Marburg Virus Variant Angola in Nonhuman Primates. (25th June 2018) - Woolsey, Courtney; Geisbert, Joan B; Matassov, Demetrius; Agans, Krystle N; Borisevich, Viktoriya; Cross, Robert W; Deer, Daniel J; Fenton, Karla A; Eldridge, John H; Mire, Chad E; Geisbert, Thomas W
Abstract: A recombinant vesicular stomatitis virus (rVSV) expressing the Marburg virus (MARV) Musoke variant glycoprotein fully protects macaques against 2 MARV variants and Ravn virus as a preventive vaccine and MARV variant Musoke as a postexposure treatment. To evaluate postexposure efficacy against the most pathogenic MARV variant, Angola, we engineered rVSVs expressing homologous Angola glycoprotein. Macaques were challenged with high or low doses of variant Angola and treated 20–30 minutes after exposure. A total of 25% and 60%–75% of treated macaques survived the high-dose and low-dose challenges, respectively. The more rapid disease progression of variant Angola versus variant Musoke may account for the incomplete protection observed.